Charge screening-controlled Verwey phase transition in Fe3O4/SrTiO3 heterostructure. (21st February 2018) - Ji, H; Wang, Y G; Li, Y
Abstract: Despite intensive investigations into the Verwey phase transition of Fe3 O4 over half a century, the mechanism of this phase transition remains controversial and needs further research. In this work, we build the Fe3 O4 /SrTiO3 multiferroic heterostructure and investigate the temperature dependence of its saturation magnetization under various electric fields. It is found that the charge-screening effect not only influences the magnetization but also induces the temperature of the Verwey phase transition shifting 13 K. It suggests that the Verwey phase transition has certain correlations with the electron distribution and the change of the number of minority spin electrons in the trimerons plays a dominant role in the temperature shift of the phase transition.